Recommendations for radiation therapy in oligometastatic prostate cancer: An ESTRO-ACROP Delphi consensus. (November 2022) - Zilli, Thomas; Achard, Vérane; Dal Pra, Alan; Schmidt-Hegemann, Nina; Jereczek-Fossa, Barbara Alicja; Lancia, Andrea; Ingrosso, Gianluca; Alongi, Filippo; Aluwini, Shafak; Arcangeli, Stefano; Blanchard, Pierre; Conde Moreno, Antonio; et al.
Highlights: PSMA PET is the preferred imaging modality for prostate cancer (PCa). Metastasis-directed radiotherapy (MDRT) may be considered for up to 5 PCa lesions. Comprehensive irradiation with systemic therapy for de novo oligometastatic PCa. MDRT without switch of systemic therapy for oligoprogressive castration-resistant PCa. Abstract: Background and purpose: Oligometastatic prostate cancer is a new and emerging treatment field with only few prospective randomized studies published so far. Despite the lack of strong level I evidence, metastasis-directed therapies (MDT) are widely used in clinical practice, mainly based on retrospective and small phase 2 studies and with a large difference across centers. Pending results of ongoing prospective randomized trials, there is a clear need for more consistent treatment indications and radiotherapy practices. Material and methods: A European Society for Radiotherapy and Oncology (ESTRO) Guidelines Committee consisting of radiation oncologists' experts in prostate cancer was asked to answer a dedicated questionnaire, including 41 questions on the main controversial issues with regard to oligometastatic prostate cancer. Results: The panel achieved consensus on patient selection and routine use of prostate-specific membrane antigen positron emission tomography (PSMA PET) imaging as preferred staging and restaging imaging. MDT strategies are recommended in the de novo oligometastatic, oligorecurrent and oligoprogressive disease setting for nodal, bone and visceral metastases. Radiation therapy doses, volumes and techniques were discussed and commented. Conclusion: These recommendations have the purpose of providing standardization and consensus to optimize the radiotherapy treatment of oligometastatic prostate cancer until mature results of randomized trials are available.